TEACHER STRATEGIES IN MANAGING STUDENTS' LEARNING INTEREST IN THE INDEPENDENT CURRICULUM - Dina Destari; Erna Adita Kusumawati; Ismaul Fitroh; Rhisty Frida Utami (CV. ADIBA AISHA AMIRA, 2024)
This research examines the strategies used by teachers in managing students' learning interest in the context of the Independent Curriculum through a review of relevant literature. The Merdeka Curriculum, which emphasizes flexibility and freedom of learning, requires teachers to apply innovative and adaptive approaches in order to motivate and optimize students' potential. Through analysis of various literature sources, this research identified three main effective strategies: (1) Differentiated Learning, which adapts learning activities to each student's abilities and learning style to ensure full engagement; (2) Professional Development, where teachers actively improve skills and knowledge through ongoing training and involvement in professional communities; and (3) Inclusive Learning Environments, which create classrooms that support diversity and facilitate the development of students' social and emotional skills. The conclusion of this research shows that the application of these strategies by teachers can significantly increase students' interest in learning, create a more dynamic learning environment, and support the achievement of better learning outcomes within the Independent Curriculum framework. These findings provide important insights for educational practitioners and policy makers in efforts to improve the quality of learning in an era of more independent and inclusive education.